2014
DOI: 10.1021/am500489x
|View full text |Cite
|
Sign up to set email alerts
|

Morphologically Controlled Synthesis of Porous Spherical and Cubic LaMnO3 with High Activity for the Catalytic Removal of Toluene

Abstract: A morphology-controlled molten salt route was developed to synthesize porous spherical LaMnO3 and cubic LaMnO3 nanoparticles using the as-prepared porous Mn2O3 spheres as template. The porous LaMnO3 spheres with an average pore size of about 34.7 nm and the cubic LaMnO3 nanoparticles with a good dispersion were confirmed by scanning electron microscope, transmission electron microscope, and N2 adsorption-desorption measurements. The mechanism of morphological transformation from the porous spherical structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…The molar ratio of La/Mn on the surface was higher than the nominal values for cubic LaMnO 3:15 , indicating that La enrichment occurred on the surface. Similar phenomenon has been reported by Wang et al 18 and Hammami et al 25 For LSMO nanoparticles, the molar ratio of La/Mn on the surface decreased below the nominal values with Sr-doping, whereas the molar ratio of Sr/ (LaþMnþSr) increased to exceed the nominal values to form Sr enrichment on the surface. Despite the surface Sr enrichment over LSMO sample, XRD analysis did not reveal the presence of di®raction peaks which were attributed to chemical compounds including strontium element, which could be due to the low quantity of those species on the sample surface.…”
Section: Physicochemical Propertiessupporting
confidence: 87%
See 1 more Smart Citation
“…The molar ratio of La/Mn on the surface was higher than the nominal values for cubic LaMnO 3:15 , indicating that La enrichment occurred on the surface. Similar phenomenon has been reported by Wang et al 18 and Hammami et al 25 For LSMO nanoparticles, the molar ratio of La/Mn on the surface decreased below the nominal values with Sr-doping, whereas the molar ratio of Sr/ (LaþMnþSr) increased to exceed the nominal values to form Sr enrichment on the surface. Despite the surface Sr enrichment over LSMO sample, XRD analysis did not reveal the presence of di®raction peaks which were attributed to chemical compounds including strontium element, which could be due to the low quantity of those species on the sample surface.…”
Section: Physicochemical Propertiessupporting
confidence: 87%
“…Raciulete and Afanasiev 17 prepared Mn-Zr and Mn-Ti supported oxide catalysts in molten Na(K)NO 3°u xes at 500 C and found that molten salt route demonstrated advantageous catalytic activity as compared to the reference catalysts. Meanwhile, it was reported by Wang et al 18 that porous spherical and cubic LaMnO 3 nanoparticles were synthesized via a morphology-controlled molten salt route. The results indicated that the porous spherical and cubic LaMnO 3 catalysts performed high catalytic performance for the combustion of toluene.…”
Section: Introductionmentioning
confidence: 99%
“…17 On the other hand, it has been recently identified as one of the most suitable catalyst for electrochemical oxygen reduction reactions, 18 and for the oxidative removal of toluene. 19 Therefore, it will be very important the development of affordable techniques for deposition of LaMnO3 thin 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 2 films, with a large surface/volume ratio, and free of defects over large areas.…”
Section: Introductionmentioning
confidence: 99%
“…The TMSS method has been used to obtain perovskites with 3D morphologies, for example, porous spherical and cubic LaMnO 3 from porous Mn 2 O 3 precursors in a mixture of NaNO 3 and KNO 3 . 59 There is another example, in which Xing et al obtained KNbO 3 hollow spheres from Nb 2 O 5 hollow spheres via the TMSS method ( Fig. 4 ).…”
Section: Morphology Of Perovskite Compounds Controlled By Tmssmentioning
confidence: 99%